Antibacterial and waterproof polymer material for tablecloth and preparation method thereof

By calendering modified polyester, zinc chloride, modified silver-loaded porous nanomagnesium oxide and azobisisobutyronitrile and other materials, the function of tablecloth fabrics in the prior art has been solved. and complex production problems achieve efficient slow-release sterilization, waterproofing and wear resistance, extending service life and reducing pollution.

CN118374135BActive Publication Date: 2024-12-17DONGGUAN IUIU HOUSEHOLD PROD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410522948.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-28
Publication Date
2024-12-17
Estimated Expiration
2044-04-28

AI Technical Summary

Technical Problem

The functional effect of existing tablecloth fabrics is reduced after multiple washes, the service life is reduced, and the production process is complex, and there are pollution problems, making it difficult to meet the requirements of continuous use and environmental protection.

Method used

Antibacterial and waterproof polymer materials for tablecloths are made by mixing modified polyester, zinc chloride, modified silver-loaded porous nanomagnesium oxide and azobisisobutyronitrile. The nano-loaded silver and silane coupling agent are improved. The material's sustained release sterilization, waterproofing and wear resistance.

Benefits of technology

It has achieved the improvement of slow-release sterilization, waterproofing, self-repairing and wear resistance of tablecloth materials, extended service life, simplified production processes, reduced pollution, and met environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The invention discloses an antibacterial and waterproof polymer material for tablecloths and a preparation method thereof, and relates to the technical field of polymer materials. When preparing the antibacterial and waterproof polymer material for tablecloths, the present invention prepares magnesium nitrate hexahydrate into porous nano magnesium oxide by a gel method, and loads silver ions, and then reacts with 3-butylene triethoxysilane and vinyl tetramethyl disiloxane in sequence to obtain modified silver-carrying porous nano magnesium oxide; terephthalic acid, 5-nitro-1,3-phthalic acid and ethylene glycol are reacted to obtain nitro polyester and then reduced to amino polyester; amino polyester and 1-allyl-1H-benzimidazole-2-formaldehyde are reacted to obtain modified polyester; modified polyester, zinc chloride, modified silver-carrying porous nano magnesium oxide and azobisisobutyronitrile are mixed and rolled to prepare antibacterial and waterproof polymer material for tablecloths. The antibacterial and waterproof polymer material for tablecloths prepared by the present invention has excellent sustained-release bactericidal performance, waterproof performance, self-repairing performance and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to an antibacterial and waterproof polymer material for tablecloths and a preparation method thereof. Background Art

[0002] Currently, the mainstream tablecloth fabrics are roughly divided into two categories: natural tablecloths and plastic tablecloths. Natural tablecloths are mostly made of woven fabrics such as pure cotton, linen, and nylon-cotton blended fibers. These fabrics are natural in style, naturally degradable, and restore the natural effect of the fabric itself as much as possible. However, cotton and linen fibers are rich in hydroxyl groups and have good hydrophilicity. As tablecloths, they are easily polluted by various factors such as tea, water, and oil. They are not easy to clean and do not have good physical and chemical properties. After several washings, the functional effects are reduced and the service life is shortened, which easily leads to excessive waste of resources.

[0003] As the concept of green environmental protection becomes more and more popular, people have higher and higher requirements for the continuous use of protective products, which not only require good performance but also long-lasting effectiveness. Common plastic tablecloths in life are made of powdered polyvinyl chloride resin, which is processed by simple physical blending methods by adding plasticizers, antioxidants and stabilizers. The effect is achieved by using additives, which increases the production process and process pollution, which is not conducive to sustainable development. Therefore, the present invention prepares an antibacterial and waterproof polymer material for tablecloths with excellent sustained-release bactericidal properties, waterproof properties, self-repairing properties and wear resistance. Summary of the invention

[0004] The object of the present invention is to provide an antibacterial and waterproof polymer material for tablecloth and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The invention discloses an antibacterial and waterproof polymer material for tablecloth, characterized in that the antibacterial and waterproof polymer material for tablecloth is obtained by mixing modified polyester, zinc chloride, modified silver-loaded porous nano magnesium oxide and azobisisobutyronitrile and then calendering.

[0007] As an optimization, the modified polyester is obtained by reducing terephthalic acid, 5-nitro-1,3-phthalic acid and ethylene glycol to form an amino polyester, and then reacting with 1-allyl-1H-benzimidazole-2-carboxaldehyde.

[0008] As an optimization, the modified silver-loaded porous nano-magnesium oxide is prepared by a gel method using magnesium nitrate hexahydrate to form porous nano-magnesium oxide, which is then loaded with nano-silver, and then reacted with 3-butylenetriethoxysilane and vinyltetramethyldisiloxane in sequence.

[0009] A method for preparing an antibacterial and waterproof polymer material for tablecloths comprises the following preparation steps:

[0010] (1) Magnesium nitrate hexahydrate, citric acid and deionized water were mixed in a mass ratio of 1:(0.7-0.9):(3-5), stirred at 75-85°C and 100-200 rpm for 3-5 h, allowed to stand at 145-155°C for 1-3 h, naturally cooled to room temperature, ground and sieved with 300-400 mesh, heated to 550-650°C at a rate of 1-3°C / min, kept warm for 1-3 h, and naturally cooled to room temperature to obtain porous nanoparticles. Magnesium oxide; mixing porous nano-magnesium oxide and anhydrous ethanol in a mass ratio of 1: (9-11), stirring at 20-30° C. and 100-200 rpm for 30-40 min, adding a silver nitrate mixture of 14-16 times the mass of the porous nano-magnesium oxide at a uniform speed within 20-30 min, continuing to stir for 3-5 hours and then centrifuging, washing with anhydrous ethanol for 3-5 times, and drying at 55-65° C. for 47-49 hours to obtain silver-loaded porous nano-magnesium oxide;

[0011] (2) 3-Butenetriethoxysilane and 45-55% ethanol solution by volume are mixed in a mass ratio of 1:(8-10), the pH value of the solution is adjusted to 3-4 with glacial acetic acid, and ultrasonic dispersion is performed for 20-40 minutes to obtain 3-Butenetriethoxysilane alcoholysis solution; silver-loaded porous nano-magnesium oxide and anhydrous ethanol are mixed in a mass ratio of 1:(24-26), and ultrasonic dispersion is performed for 25-35 minutes, 3-Butenetriethoxysilane alcoholysis solution with a mass of 3-4 times of the mass of silver-loaded porous nano-magnesium oxide is added, and the mixture is stirred at 75-85° C. and 410-430 r / min for 3-5 hours, and then filtered, and the mixture is filtered with anhydrous ethanol. The pre-modified silver-loaded porous nano-magnesium oxide is prepared by washing with ethanol and deionized water for 3 to 5 times, drying at 70 to 80° C. for 6 to 8 hours, and obtaining a pre-modified silver-loaded porous nano-magnesium oxide; the pre-modified silver-loaded porous nano-magnesium oxide, vinyltetramethyldisiloxane, chloroplatinic acid and toluene are mixed in a mass ratio of 1:(1.4 to 1.6):(0.03 to 0.04):(9 to 11), stirred in a nitrogen atmosphere at 85 to 95° C. and 200 to 400 r / min for 6 to 8 hours, naturally cooled to room temperature and then centrifuged, washed with deionized water for 3 to 5 times, and dried at 45 to 55° C. for 10 to 12 hours to obtain a modified silver-loaded porous nano-magnesium oxide;

[0012] (3) terephthalic acid, 5-nitro-1,3-phthalic acid and ethylene glycol are mixed in a molar ratio of 1:1:2.1, antimony trioxide in an amount of 0.3 to 0.4 times the mass of terephthalic acid is added, and the mixture is stirred at 235 to 245° C. and 100 to 200 rpm for 2 to 4 hours under a nitrogen atmosphere, and the temperature is raised to 270 to 280° C. and 90 to 110 Pa to continue the reaction for 3 to 5 hours, and the mixture is naturally cooled to room temperature, washed with deionized water for 3 to 5 times, and dried at 65 to 75° C. for 10 to 12 hours to obtain nitropolyester; nitropolyester, palladium carbon with a palladium content of 10% and N-methylpyrrolidone are mixed in a mass ratio of 1:(0.6 to 0.8):(9 to 11), and the mixture is stirred at 20 to 30° C. and 100 to 200 rpm for 23 to 25 hours under a hydrogen atmosphere, and then filtered, and the nitropolyester is added. 99-101 times of deionized water, let stand until the precipitate mass remains unchanged, then filter, and dry at 65-75°C for 6-8h to obtain amino polyester; amino polyester, glacial acetic acid and N,N-dimethylformamide are mixed in a mass ratio of 1:(0.01-0.02):(8-10), stirred at 20-30°C and 200-300rpm for 1-2h, heated to 75-85°C, 1-allyl-1H-benzimidazole-2-carboxaldehyde is added, the ratio of the molar amount of aldehyde group in 1-allyl-1H-benzimidazole-2-carboxaldehyde to the molar amount of amino group in amino polyester is 1:1, continue stirring for 3-5h, cool naturally to room temperature, add methanol 86-88 times of the mass of amino polyester, let stand until the precipitate mass remains unchanged, then filter, and dry at 45-55°C for 9-11h to obtain modified polyester;

[0013] (4) The modified polyester is heated to melt at 245-255° C. by an internal mixer, zinc chloride is added, the ratio of the molar amount of zinc ions in the zinc chloride to the molar amount of nitrogen elements in the modified polyester is 1:6, and the mixture is stirred at 100-200 rpm for 5-15 min. 0.6-0.8 times the mass of the modified polyester of modified silver-loaded porous nano-magnesium oxide and 0.01-0.02 times the mass of the modified polyester of azobisisobutyronitrile are added, stirring is continued for 10-20 min, and the mixture is rolled to a thickness of 0.4-0.6 mm by a calender, and the mixture is allowed to stand at 120-130° C. for 10-12 h, and naturally cooled to room temperature to obtain an antibacterial and waterproof polymer material for tablecloths.

[0014] As an optimization, the silver nitrate mixed solution is obtained by mixing silver nitrate, polyvinyl pyrrolidone and anhydrous ethanol in a mass ratio of 1:(1-3):(58-60), and stirring at 20-30° C. and 100-200 rpm for 3-5 hours.

[0015] As an optimization, the reaction equation of the pre-modified silver-loaded porous nano-magnesium oxide in step (2) is:

[0016]

[0017] As an optimization, the reaction equation for the modified silver-loaded porous nano-magnesium oxide in step (2) is:

[0018]

[0019] As an optimization, the structure of the nitropolyester in step (3) is as follows:

[0020]

[0021] As an optimization, the palladium carbon with a palladium content of 10% in step (3) comes from Hubei Xinrunde Chemical Co., Ltd.

[0022] As an optimization, the structure of the amino polyester in step (3) is as follows:

[0023]

[0024] As an optimization, the reaction equation of the modified polyester in step (3) is:

[0025]

[0026] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0027] When preparing the antibacterial and waterproof polymer material for tablecloth, the invention comprises the following steps: preparing porous nano magnesium oxide from magnesium nitrate hexahydrate by a gel method, and then loading nano silver on the porous nano magnesium oxide to obtain the silver-loaded porous nano magnesium oxide; reacting the silver-loaded porous nano magnesium oxide with 3-butylenetriethoxysilane and vinyltetramethyldisiloxane in sequence to obtain modified silver-loaded porous nano magnesium oxide; reacting terephthalic acid, 5-nitro-1,3-phthalic acid and ethylene glycol to obtain nitro polyester, and then reducing the nitro polyester to obtain amino polyester; reacting the amino polyester with 1-allyl-1H-benzimidazole-2-carboxaldehyde to obtain modified polyester; and mixing the modified polyester, zinc chloride, the modified silver-loaded porous nano magnesium oxide and azobisisobutyronitrile and rolling the mixture to obtain the antibacterial and waterproof polymer material for tablecloth.

[0028] Firstly, magnesium nitrate hexahydrate is prepared into porous nano-magnesium oxide by a gel method, and then nano-silver is loaded to obtain silver-loaded porous nano-magnesium oxide; the silver-loaded porous nano-magnesium oxide is reacted with 3-butylenetriethoxysilane and vinyltetramethyldisiloxane in sequence to obtain modified silver-loaded porous nano-magnesium oxide; the porous nano-magnesium oxide is used as a carrier, oxygen vacancies and magnesium vacancies on the surface are used for oxidation and sterilization, and nano-silver is adsorbed and combined at the same time to control the release rate of silver ions, thereby improving the sustained-release sterilization performance of the antibacterial and waterproof polymer material for tablecloths; after being treated with a silane coupling agent, vinyltetramethyldisiloxane is grafted by silicon hydrogen addition to form a silicon-carbon long chain with a double bond at the end, thereby increasing a stable chemical structure, reducing the interaction with water molecules, and improving the waterproof performance and wear resistance of the antibacterial and waterproof polymer material for tablecloths; at the same time, the carbon-carbon double bond retained at the end can participate in cross-linking under thermal initiation conditions to form a stable chemical bond, thereby further improving the wear resistance of the antibacterial and waterproof polymer material for tablecloths.

[0029] Secondly, terephthalic acid, 5-nitro-1,3-phthalic acid and ethylene glycol are reacted to obtain nitro polyester, which is then reduced to obtain amino polyester; the amino polyester is then reacted with 1-allyl-1H-benzimidazole-2-carboxaldehyde to obtain modified polyester; the modified polyester, zinc chloride, modified silver-loaded porous nano-magnesium oxide and azobisisobutyronitrile are mixed and calendered to prepare an antibacterial and waterproof polymer material for tablecloths; a reactive amino group is introduced into the polyester main chain through nitro reduction, and 1-allyl-1H-benzimidazole-2-carboxaldehyde is grafted thereon by Schiff base reaction, carbon-carbon double bonds and unsaturated carbon-nitrogen double bonds are introduced, the coordination ability with metal ions is enhanced, zinc ions are complexed, and the self-repairing performance of the antibacterial and waterproof polymer material for tablecloths is improved; at the same time, it can participate in heat-induced crosslinking, form a stable chemical bond with the modified silver-loaded porous nano-magnesium oxide, improve strength, durability and deformation ability, and enhance the wear resistance of the antibacterial and waterproof polymer material for tablecloths. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the index testing methods of the antibacterial and waterproof polymer material for tablecloths prepared in the following examples are as follows:

[0032] Sustained-release bactericidal performance: The antibacterial and waterproof polymer material for tablecloths obtained in each embodiment and the comparative example were immersed in deionized water, shaken at 25°C and 150r / min for 5 days, taken out, and dried at 50°C for 8h to obtain test samples; Escherichia coli culture liquid was prepared according to GB / T31402; 100 μL of 10% ethanol was evenly coated on a nutrient agar culture dish with a diameter of 10 cm. 6 The test samples were added into the Escherichia coli solution with CFU / mL at intervals and cultured at 34℃ for 24h. The diameter of the inhibition zone was measured to determine the sustained-release bactericidal performance.

[0033] Waterproof performance: Take 2cm*2cm test samples of the antibacterial and waterproof polymer material for tablecloths obtained in each embodiment and the comparative example, and test the water contact angle with a dynamic and static contact angle meter at 25°C and a rotating water drop volume of 3μL to determine the waterproof performance.

[0034] Self-repairing performance: Take 10cm*5cm test samples of the antibacterial and waterproof tablecloth polymer material obtained in each embodiment and the comparative example, scratch a 2cm long and 0.3mm deep scratch with a needle, let it stand at 25℃ for 48h, and measure the repair rate.

[0035] Wear resistance: Take 10cm*10cm test samples of the antibacterial and waterproof polymer material for tablecloths obtained in each embodiment and the comparative example, fix them on a reciprocating linear abrasion tester, and use flannel cloth to wear at a rate of 40 cycles / min and a load of 1kg / cm 2 After 200 cycles, the degree of surface damage was recorded by atomic force microscopy (0: no scratches, 1: slight scratches, 2: severe scratches) to determine the wear resistance.

[0036] Example 1

[0037] A method for preparing an antibacterial and waterproof polymer material for tablecloths, the method comprising the following preparation steps:

[0038] (1) Magnesium nitrate hexahydrate, citric acid and deionized water are mixed in a mass ratio of 1:0.7:3, stirred at 75°C and 100 rpm for 5 hours, allowed to stand at 145°C for 3 hours, naturally cooled to room temperature, ground and sieved through 300 mesh, heated to 550°C at a rate of 1°C / min and kept warm for 3 hours, and naturally cooled to room temperature to obtain porous nano-magnesium oxide; porous nano-magnesium oxide and anhydrous ethanol are mixed in a mass ratio of 1:9, stirred at 20°C and 100 rpm for 40 minutes, and a silver nitrate mixture of 14 times the mass of the porous nano-magnesium oxide is uniformly added within 20 minutes, stirred for 5 hours, centrifuged, washed with anhydrous ethanol 3 times, and dried at 55°C for 49 hours to obtain silver-loaded porous nano-magnesium oxide;

[0039] (2) 3-Butenetriethoxysilane and 45% ethanol solution were mixed at a mass ratio of 1:8, the pH of the solution was adjusted to 3 with glacial acetic acid, and ultrasonic dispersion was performed for 20 minutes to obtain 3-Butenetriethoxysilane alcoholysis solution; silver-loaded porous nano-magnesium oxide and anhydrous ethanol were mixed at a mass ratio of 1:24, and ultrasonic dispersion was performed for 25 minutes, and 3-Butenetriethoxysilane alcoholysis solution with a mass of 3 times that of silver-loaded porous nano-magnesium oxide was added, and stirred at 75°C and 410 r / min for 5 hours. Filter, wash with anhydrous ethanol and deionized water for 3 times respectively, and dry at 70°C for 8h to obtain pre-modified silver-loaded porous nano-magnesium oxide; mix the pre-modified silver-loaded porous nano-magnesium oxide, vinyltetramethyldisiloxane, chloroplatinic acid and toluene in a mass ratio of 1:1.4:0.03:9, stir for 8h at 85°C and 200r / min in a nitrogen atmosphere, cool naturally to room temperature and then centrifuge, wash with deionized water for 3 times, and dry at 45°C for 12h to obtain modified silver-loaded porous nano-magnesium oxide;

[0040] (3) Terephthalic acid, 5-nitro-1,3-phthalic acid and ethylene glycol were mixed in a molar ratio of 1:1:2.1, antimony trioxide (0.3 times the mass of terephthalic acid) was added, and the mixture was stirred at 235°C and 100 rpm for 4 h in a nitrogen environment, and the temperature was raised to 270°C and 90 Pa to continue the reaction for 5 h, and the mixture was naturally cooled to room temperature, washed with deionized water for 3 times, and dried at 65°C for 12 h to obtain nitropolyester; nitropolyester, palladium carbon with a palladium content of 10% and N-methylpyrrolidone were mixed in a mass ratio of 1:0.6:9, and the mixture was stirred at 20°C and 100 rpm for 25 h in a hydrogen atmosphere, and then filtered, and deionized water (99 times the mass of nitropolyester) was added to the mixture. deionized water, let stand until the precipitate mass remains unchanged, filter, and dry at 65°C for 8h to obtain amino polyester; mix amino polyester, glacial acetic acid and N,N-dimethylformamide in a mass ratio of 1:0.01:8, stir at 20°C and 200rpm for 2h, heat to 75°C, add 1-allyl-1H-benzimidazole-2-carboxaldehyde, the ratio of the molar amount of aldehyde groups in 1-allyl-1H-benzimidazole-2-carboxaldehyde to the molar amount of amino groups in amino polyester is 1:1, continue stirring for 5h, cool naturally to room temperature, add methanol 86 times the mass of amino polyester, let stand until the precipitate mass remains unchanged, filter, and dry at 45°C for 11h to obtain modified polyester;

[0041] (4) The modified polyester was heated to melt at 245° C. using an internal mixer, and zinc chloride was added, wherein the ratio of the molar amount of zinc ions in the zinc chloride to the molar amount of nitrogen elements in the modified polyester was 1:6. The mixture was stirred at 100 rpm for 15 min, and 0.6 times the mass of the modified polyester of modified silver-loaded porous nano-magnesium oxide and 0.01 times the mass of the modified polyester of azobisisobutyronitrile were added. The mixture was stirred for 20 min, and the mixture was rolled to a thickness of 0.4 mm using a calender, and allowed to stand at 120° C. for 12 h, and naturally cooled to room temperature to obtain an antibacterial and waterproof polymer material for tablecloths.

[0042] Example 2

[0043] A method for preparing an antibacterial and waterproof polymer material for tablecloths, the method comprising the following preparation steps:

[0044] (1) Magnesium nitrate hexahydrate, citric acid and deionized water are mixed in a mass ratio of 1:0.8:4, stirred at 80°C and 150 rpm for 4 hours, allowed to stand at 150°C for 2 hours, naturally cooled to room temperature, ground and sieved to 350 mesh, heated to 600°C at a rate of 2°C / min and kept warm for 2 hours, and naturally cooled to room temperature to obtain porous nano-magnesium oxide; porous nano-magnesium oxide and anhydrous ethanol are mixed in a mass ratio of 1:10, stirred at 25°C and 150 rpm for 35 minutes, and a silver nitrate mixture of 15 times the mass of the porous nano-magnesium oxide is uniformly added within 25 minutes, stirred for 4 hours, centrifuged, washed with anhydrous ethanol 4 times, and dried at 60°C for 48 hours to obtain silver-loaded porous nano-magnesium oxide;

[0045] (2) 3-Butenetriethoxysilane and 50% ethanol solution by volume fraction were mixed in a mass ratio of 1:9, the pH of the solution was adjusted to 3.5 with glacial acetic acid, and ultrasonic dispersion was performed for 30 minutes to obtain 3-Butenetriethoxysilane alcoholysis solution; silver-loaded porous nano-magnesium oxide and anhydrous ethanol were mixed in a mass ratio of 1:25, and ultrasonic dispersion was performed for 30 minutes, and 3-Butenetriethoxysilane alcoholysis solution with a mass of 3.5 times that of silver-loaded porous nano-magnesium oxide was added, and stirred at 80°C and 420 r / min for 4 hours. Filter, wash with anhydrous ethanol and deionized water for 4 times respectively, and dry at 75°C for 7h to obtain pre-modified silver-loaded porous nano-magnesium oxide; mix the pre-modified silver-loaded porous nano-magnesium oxide, vinyltetramethyldisiloxane, chloroplatinic acid and toluene in a mass ratio of 1:1.5:0.035:10, stir at 90°C and 300r / min for 7h in a nitrogen atmosphere, cool naturally to room temperature and then centrifuge, wash with deionized water for 4 times, and dry at 50°C for 11h to obtain modified silver-loaded porous nano-magnesium oxide;

[0046] (3) Terephthalic acid, 5-nitro-1,3-phthalic acid and ethylene glycol were mixed in a molar ratio of 1:1:2.1, antimony trioxide (0.35 times the mass of terephthalic acid) was added, and the mixture was stirred at 240°C and 150 rpm for 3 h in a nitrogen environment, and the temperature was raised to 275°C and 100 Pa for further reaction for 4 h, and the mixture was naturally cooled to room temperature, washed with deionized water for 4 times, and dried at 70°C for 11 h to obtain nitropolyester; nitropolyester, palladium carbon with a palladium content of 10% and N-methylpyrrolidone were mixed in a mass ratio of 1:0.7:10, and the mixture was stirred at 25°C and 150 rpm for 24 h in a hydrogen atmosphere, and then filtered, and 100 times the mass of nitropolyester was added. Deionized water, let stand until the precipitate mass remains unchanged, filter, and dry at 70°C for 7h to obtain amino polyester; mix amino polyester, glacial acetic acid and N,N-dimethylformamide in a mass ratio of 1:0.015:9, stir at 25°C and 250rpm for 1.5h, heat to 80°C, add 1-allyl-1H-benzimidazole-2-carboxaldehyde, the ratio of the molar amount of aldehyde groups in 1-allyl-1H-benzimidazole-2-carboxaldehyde to the molar amount of amino groups in amino polyester is 1:1, continue stirring for 4h, cool naturally to room temperature, add methanol 87 times the mass of amino polyester, let stand until the precipitate mass remains unchanged, filter, and dry at 50°C for 10h to obtain modified polyester;

[0047] (4) The modified polyester was heated to melt at 250° C. using an internal mixer, and zinc chloride was added, wherein the ratio of the molar amount of zinc ions in the zinc chloride to the molar amount of nitrogen elements in the modified polyester was 1:6. The mixture was stirred at 150 rpm for 10 min, and 0.7 times the mass of the modified polyester of modified silver-loaded porous nano-magnesium oxide and 0.015 times the mass of the modified polyester of azobisisobutyronitrile were added. The mixture was stirred for 15 min, and the mixture was rolled to a thickness of 0.5 mm using a calender, and allowed to stand at 125° C. for 11 h, and naturally cooled to room temperature to obtain an antibacterial and waterproof polymer material for tablecloths.

[0048] Example 3

[0049] A method for preparing an antibacterial and waterproof polymer material for tablecloths, the method comprising the following preparation steps:

[0050] (1) Magnesium nitrate hexahydrate, citric acid and deionized water are mixed in a mass ratio of 1:0.9:5, stirred at 85°C and 200 rpm for 3 h, allowed to stand at 155°C for 1 h, naturally cooled to room temperature, ground and sieved through 400 mesh, heated to 650°C at a rate of 3°C / min and kept warm for 1 h, and naturally cooled to room temperature to obtain porous nano-magnesium oxide; porous nano-magnesium oxide and anhydrous ethanol are mixed in a mass ratio of 1:11, stirred at 30°C and 200 rpm for 30 min, and a silver nitrate mixture of 16 times the mass of the porous nano-magnesium oxide is uniformly added within 30 min, stirred for 3 h, centrifuged, washed with anhydrous ethanol 5 times, and dried at 65°C for 47 h to obtain silver-loaded porous nano-magnesium oxide;

[0051] (2) 3-Butenetriethoxysilane and 55% ethanol solution were mixed at a mass ratio of 1:10, the pH of the solution was adjusted to 4 with glacial acetic acid, and ultrasonic dispersion was performed for 40 minutes to obtain 3-Butenetriethoxysilane alcoholysis solution; silver-loaded porous nano-magnesium oxide and anhydrous ethanol were mixed at a mass ratio of 1:26, and ultrasonic dispersion was performed for 35 minutes, and 3-Butenetriethoxysilane alcoholysis solution with a mass of 4 times that of silver-loaded porous nano-magnesium oxide was added, and stirred at 85°C and 430 r / min for 3 hours. Filter, wash with anhydrous ethanol and deionized water for 5 times respectively, and dry at 80°C for 6 hours to obtain pre-modified silver-loaded porous nano-magnesium oxide; mix the pre-modified silver-loaded porous nano-magnesium oxide, vinyltetramethyldisiloxane, chloroplatinic acid and toluene in a mass ratio of 1:1.6:0.04:11, stir for 6 hours at 95°C and 400r / min in a nitrogen atmosphere, cool naturally to room temperature and then centrifuge, wash with deionized water for 5 times, and dry at 55°C for 10 hours to obtain modified silver-loaded porous nano-magnesium oxide;

[0052] (3) Terephthalic acid, 5-nitro-1,3-phthalic acid and ethylene glycol were mixed in a molar ratio of 1:1:2.1, antimony trioxide (0.4 times the mass of terephthalic acid) was added, and the mixture was stirred at 245°C and 200 rpm for 2 h in a nitrogen environment, and the temperature was raised to 280°C and 110 Pa to continue the reaction for 3 h, and the mixture was naturally cooled to room temperature, washed with deionized water for 5 times, and dried at 75°C for 10 h to obtain nitropolyester; nitropolyester, palladium carbon with a palladium content of 10% and N-methylpyrrolidone were mixed in a mass ratio of 1:0.8:11, stirred at 30°C and 200 rpm for 23 h in a hydrogen atmosphere, and then filtered, and 101 times the mass of nitropolyester was added. of deionized water, let stand until the precipitate mass remains unchanged, filter, and dry at 75°C for 6 hours to obtain amino polyester; mix the amino polyester, glacial acetic acid and N,N-dimethylformamide in a mass ratio of 1:0.02:10, stir at 30°C and 300rpm for 1 hour, heat to 85°C, add 1-allyl-1H-benzimidazole-2-carboxaldehyde, the ratio of the molar amount of aldehyde groups in 1-allyl-1H-benzimidazole-2-carboxaldehyde to the molar amount of amino groups in the amino polyester is 1:1, continue stirring for 3 hours, cool naturally to room temperature, add methanol 88 times the mass of the amino polyester, let stand until the precipitate mass remains unchanged, filter, and dry at 55°C for 9 hours to obtain modified polyester;

[0053] (4) The modified polyester was heated to melt at 255° C. using an internal mixer, and zinc chloride was added, wherein the ratio of the molar amount of zinc ions in the zinc chloride to the molar amount of nitrogen elements in the modified polyester was 1:6. The mixture was stirred at 200 rpm for 5 min, and 0.8 times the mass of the modified polyester of modified silver-loaded porous nano-magnesium oxide and 0.02 times the mass of the modified polyester of azobisisobutyronitrile were added. The mixture was stirred for 10 min, and the mixture was rolled to a thickness of 0.6 mm using a calender, and allowed to stand at 130° C. for 10 h, and naturally cooled to room temperature to obtain an antibacterial and waterproof polymer material for tablecloths.

[0054] Comparative Example 1

[0055] A method for preparing an antibacterial and waterproof polymer material for tablecloths, the method comprising the following preparation steps:

[0056] (1) Magnesium nitrate hexahydrate, citric acid and deionized water were mixed in a mass ratio of 1:0.8:4, stirred at 80°C and 150 rpm for 4 h, allowed to stand at 150°C for 2 h, naturally cooled to room temperature, ground and sieved with 350 mesh, heated to 600°C at a rate of 2°C / min, kept warm for 2 h, and naturally cooled to room temperature to obtain porous nano-magnesium oxide;

[0057] (2) 3-Butenetriethoxysilane and 50% ethanol solution by volume were mixed in a mass ratio of 1:9, the pH of the solution was adjusted to 3.5 with glacial acetic acid, and ultrasonic dispersion was performed for 30 minutes to obtain 3-Butenetriethoxysilane alcoholysis solution; porous nano-magnesium oxide and anhydrous ethanol were mixed in a mass ratio of 1:25, ultrasonic dispersion was performed for 30 minutes, 3-Butenetriethoxysilane alcoholysis solution with a mass of 3.5 times that of porous nano-magnesium oxide was added, and stirred at 80°C and 420 r / min for 4 hours. After filtering, washing with anhydrous ethanol and deionized water for 4 times respectively, and drying at 75°C for 7h to obtain pre-modified porous nano-magnesium oxide; pre-modified porous nano-magnesium oxide, vinyltetramethyldisiloxane, chloroplatinic acid and toluene were mixed in a mass ratio of 1:1.5:0.035:10, stirred for 7h at 90°C and 300r / min in a nitrogen atmosphere, naturally cooled to room temperature and then centrifuged, washed with deionized water for 4 times, and dried at 50°C for 11h to obtain modified porous nano-magnesium oxide;

[0058] (3) Terephthalic acid, 5-nitro-1,3-phthalic acid and ethylene glycol were mixed in a molar ratio of 1:1:2.1, antimony trioxide (0.35 times the mass of terephthalic acid) was added, and the mixture was stirred at 240°C and 150 rpm for 3 h in a nitrogen environment, and the temperature was raised to 275°C and 100 Pa for further reaction for 4 h, and the mixture was naturally cooled to room temperature, washed with deionized water for 4 times, and dried at 70°C for 11 h to obtain nitropolyester; nitropolyester, palladium carbon with a palladium content of 10% and N-methylpyrrolidone were mixed in a mass ratio of 1:0.7:10, and the mixture was stirred at 25°C and 150 rpm for 24 h in a hydrogen atmosphere, and then filtered, and 100 times the mass of nitropolyester was added. Deionized water, let stand until the precipitate mass remains unchanged, filter, and dry at 70°C for 7h to obtain amino polyester; mix amino polyester, glacial acetic acid and N,N-dimethylformamide in a mass ratio of 1:0.015:9, stir at 25°C and 250rpm for 1.5h, heat to 80°C, add 1-allyl-1H-benzimidazole-2-carboxaldehyde, the ratio of the molar amount of aldehyde groups in 1-allyl-1H-benzimidazole-2-carboxaldehyde to the molar amount of amino groups in amino polyester is 1:1, continue stirring for 4h, cool naturally to room temperature, add methanol 87 times the mass of amino polyester, let stand until the precipitate mass remains unchanged, filter, and dry at 50°C for 10h to obtain modified polyester;

[0059] (4) The modified polyester was heated to melt at 250°C using an internal mixer, and zinc chloride was added, wherein the ratio of the molar amount of zinc ions in the zinc chloride to the molar amount of nitrogen elements in the modified polyester was 1:6. The mixture was stirred at 150 rpm for 10 min, and 0.7 times the mass of the modified polyester of modified porous nano-magnesium oxide and 0.015 times the mass of the modified polyester of azobisisobutyronitrile were added. The mixture was stirred for 15 min, and the mixture was rolled to a thickness of 0.5 mm using a calender, and allowed to stand at 125°C for 11 h, and naturally cooled to room temperature to obtain an antibacterial and waterproof polymer material for tablecloths.

[0060] Comparative Example 2

[0061] A method for preparing an antibacterial and waterproof polymer material for tablecloths, the method comprising the following preparation steps:

[0062] (1) Magnesium nitrate hexahydrate, citric acid and deionized water are mixed in a mass ratio of 1:0.8:4, stirred at 80°C and 150 rpm for 4 hours, allowed to stand at 150°C for 2 hours, naturally cooled to room temperature, ground and sieved to 350 mesh, heated to 600°C at a rate of 2°C / min and kept warm for 2 hours, and naturally cooled to room temperature to obtain porous nano-magnesium oxide; porous nano-magnesium oxide and anhydrous ethanol are mixed in a mass ratio of 1:10, stirred at 25°C and 150 rpm for 35 minutes, and a silver nitrate mixture of 15 times the mass of the porous nano-magnesium oxide is uniformly added within 25 minutes, stirred for 4 hours, centrifuged, washed with anhydrous ethanol 4 times, and dried at 60°C for 48 hours to obtain silver-loaded porous nano-magnesium oxide;

[0063] (2) 3-Butenetriethoxysilane and 50% ethanol solution by volume fraction were mixed in a mass ratio of 1:9, the pH value of the solution was adjusted to 3.5 with glacial acetic acid, and ultrasonic dispersion was performed for 30 minutes to obtain 3-Butenetriethoxysilane alcoholysis solution; silver-loaded porous nano-magnesium oxide and anhydrous ethanol were mixed in a mass ratio of 1:25, and ultrasonic dispersion was performed for 30 minutes, and 3-Butenetriethoxysilane alcoholysis solution with a mass of 3.5 times that of the silver-loaded porous nano-magnesium oxide was added, and the mixture was stirred at 80° C. and 420 r / min for 4 hours, filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 75° C. for 7 hours to obtain modified silver-loaded porous nano-magnesium oxide;

[0064] (3) Terephthalic acid, 5-nitro-1,3-phthalic acid and ethylene glycol were mixed in a molar ratio of 1:1:2.1, antimony trioxide (0.35 times the mass of terephthalic acid) was added, and the mixture was stirred at 240°C and 150 rpm for 3 h in a nitrogen environment, and the temperature was raised to 275°C and 100 Pa for further reaction for 4 h, and the mixture was naturally cooled to room temperature, washed with deionized water for 4 times, and dried at 70°C for 11 h to obtain nitropolyester; nitropolyester, palladium carbon with a palladium content of 10% and N-methylpyrrolidone were mixed in a mass ratio of 1:0.7:10, and the mixture was stirred at 25°C and 150 rpm for 24 h in a hydrogen atmosphere, and then filtered, and 100 times the mass of nitropolyester was added. Deionized water, let stand until the precipitate mass remains unchanged, filter, and dry at 70°C for 7h to obtain amino polyester; mix amino polyester, glacial acetic acid and N,N-dimethylformamide in a mass ratio of 1:0.015:9, stir at 25°C and 250rpm for 1.5h, heat to 80°C, add 1-allyl-1H-benzimidazole-2-carboxaldehyde, the ratio of the molar amount of aldehyde groups in 1-allyl-1H-benzimidazole-2-carboxaldehyde to the molar amount of amino groups in amino polyester is 1:1, continue stirring for 4h, cool naturally to room temperature, add methanol 87 times the mass of amino polyester, let stand until the precipitate mass remains unchanged, filter, and dry at 50°C for 10h to obtain modified polyester;

[0065] (4) The modified polyester was heated to melt at 250° C. using an internal mixer, and zinc chloride was added, wherein the ratio of the molar amount of zinc ions in the zinc chloride to the molar amount of nitrogen elements in the modified polyester was 1:6. The mixture was stirred at 150 rpm for 10 min, and 0.7 times the mass of the modified polyester of modified silver-loaded porous nano-magnesium oxide and 0.015 times the mass of the modified polyester of azobisisobutyronitrile were added. The mixture was stirred for 15 min, and the mixture was rolled to a thickness of 0.5 mm using a calender, and allowed to stand at 125° C. for 11 h, and naturally cooled to room temperature to obtain an antibacterial and waterproof polymer material for tablecloths.

[0066] Comparative Example 3

[0067] A method for preparing an antibacterial and waterproof polymer material for tablecloths, the method comprising the following preparation steps:

[0068] (1) Magnesium nitrate hexahydrate, citric acid and deionized water are mixed in a mass ratio of 1:0.8:4, stirred at 80°C and 150 rpm for 4 hours, allowed to stand at 150°C for 2 hours, naturally cooled to room temperature, ground and sieved to 350 mesh, heated to 600°C at a rate of 2°C / min and kept warm for 2 hours, and naturally cooled to room temperature to obtain porous nano-magnesium oxide; porous nano-magnesium oxide and anhydrous ethanol are mixed in a mass ratio of 1:10, stirred at 25°C and 150 rpm for 35 minutes, and a silver nitrate mixture of 15 times the mass of the porous nano-magnesium oxide is uniformly added within 25 minutes, stirred for 4 hours, centrifuged, washed with anhydrous ethanol 4 times, and dried at 60°C for 48 hours to obtain silver-loaded porous nano-magnesium oxide;

[0069] (2) 3-Butenetriethoxysilane and 50% ethanol solution by volume fraction were mixed in a mass ratio of 1:9, the pH of the solution was adjusted to 3.5 with glacial acetic acid, and ultrasonic dispersion was performed for 30 minutes to obtain 3-Butenetriethoxysilane alcoholysis solution; silver-loaded porous nano-magnesium oxide and anhydrous ethanol were mixed in a mass ratio of 1:25, and ultrasonic dispersion was performed for 30 minutes, and 3-Butenetriethoxysilane alcoholysis solution with a mass of 3.5 times that of silver-loaded porous nano-magnesium oxide was added, and stirred at 80°C and 420 r / min for 4 hours. Filter, wash with anhydrous ethanol and deionized water for 4 times respectively, and dry at 75°C for 7h to obtain pre-modified silver-loaded porous nano-magnesium oxide; mix the pre-modified silver-loaded porous nano-magnesium oxide, vinyltetramethyldisiloxane, chloroplatinic acid and toluene in a mass ratio of 1:1.5:0.035:10, stir at 90°C and 300r / min for 7h in a nitrogen atmosphere, cool naturally to room temperature and then centrifuge, wash with deionized water for 4 times, and dry at 50°C for 11h to obtain modified silver-loaded porous nano-magnesium oxide;

[0070] (3) Polyethylene terephthalate YS-Y01 was heated to melt at 250°C using an internal mixer, and zinc chloride was added, wherein the molar ratio of zinc ions in the zinc chloride to the molar ratio of nitrogen elements in the polyethylene terephthalate YS-Y01 was 1:6. The mixture was stirred at 150 rpm for 10 min, and 0.7 times the mass of polyethylene terephthalate YS-Y01 modified silver-loaded porous nano-magnesium oxide and 0.015 times the mass of polyethylene terephthalate YS-Y01 azobisisobutyronitrile were added. The mixture was stirred for 15 min, and the mixture was rolled to a thickness of 0.5 mm using a calender, and allowed to stand at 125°C for 11 h, and naturally cooled to room temperature to obtain an antibacterial and waterproof polymer material for tablecloths.

[0071] Effect example

[0072] Table 1 below shows the analysis results of the sustained-release bactericidal performance, waterproof performance, self-repairing performance and wear resistance of the antibacterial and waterproof polymer materials for tablecloths of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.

[0073] Table 1

[0074] Diameter of inhibition zone cm Water contact angle° Repair rate % Surface damage degree Example 1 1.47 164 93.1 0 Example 2 1.52 169 93.7 0 Example 3 1.44 167 93.4 0 Comparative Example 1 0.23 162 91.9 0 Comparative Example 2 1.39 87 92.6 -2 Comparative Example 3 1.33 163 13.7 -1

[0075] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the antibacterial and waterproof polymer material for tablecloths prepared by the present invention has good sustained-release bactericidal performance, waterproof performance, self-repairing performance and wear resistance.

[0076] By comparison, the diameters of the antibacterial zones of Examples 1, 2, and 3 are larger than those of Comparative Example 1, indicating that porous nano-magnesium oxide is used as a carrier to utilize oxygen vacancies and magnesium vacancies on the surface for oxidative sterilization, while nano-silver is adsorbed and combined to control the release rate of silver ions, thereby improving the sustained-release bactericidal performance of the antibacterial and waterproof polymer material for tablecloths.

[0077] By comparison, compared with Comparative Example 2, Examples 1, 2, and 3 have larger water contact angles and severe scratches, indicating that after the silane coupling agent treatment, vinyltetramethyldisiloxane is grafted by hydrosilylation to form a long silicon-carbon chain with a double bond at the end, which increases the stable chemical structure, reduces the interaction with water molecules, and improves the waterproof and wear resistance of the antibacterial and waterproof polymer material for tablecloths; at the same time, the carbon-carbon double bond retained at the end can participate in cross-linking under thermal initiation conditions to form a stable chemical bond, further improving the wear resistance of the antibacterial and waterproof polymer material for tablecloths.

[0078] By comparison, Examples 1, 2, and 3 have a higher repair rate than Comparative Example 3 and have slight scratches, which shows that a reactive amino group is introduced into the polyester main chain by nitro reduction, and 1-allyl-1H-benzimidazole-2-carboxaldehyde is grafted onto it by Schiff base reaction, carbon-carbon double bonds and unsaturated carbon-nitrogen double bonds are introduced, the coordination ability with metal ions is enhanced, zinc ions are complexed, and the self-repairing properties of the antibacterial and waterproof polymer material for tablecloths are improved; at the same time, it can participate in heat-induced crosslinking, and form a stable chemical bond with the modified silver-loaded porous nano-magnesium oxide, thereby improving the strength, durability and deformation ability, and enhancing the wear resistance of the antibacterial and waterproof polymer material for tablecloths.

[0079] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An antibacterial and waterproof polymer material for tablecloths, It is characterized in that The antibacterial and waterproof polymer material for tablecloth is obtained by mixing and calendering modified polyester, zinc chloride, modified silver-loaded porous nano magnesium oxide and azobisisobutyronitrile; The modified polyester is obtained by reducing terephthalic acid, 5-nitro-1,3-phthalic acid and ethylene glycol to form an amino polyester, and then reacting with 1-allyl-1H-benzimidazole-2-carboxaldehyde; The modified silver-loaded porous nano magnesium oxide is prepared by using magnesium nitrate hexahydrate through a gel method to prepare porous nano magnesium oxide, which is then loaded with nano silver, and then reacted with 3-butylene triethoxysilane and vinyl tetramethyl disiloxane in sequence to obtain the porous nano magnesium oxide.

2. A method for preparing an antibacterial and waterproof polymer material for tablecloths, It is characterized in that The method comprises the following preparation steps: (1) Magnesium nitrate hexahydrate, citric acid and deionized water were mixed in a mass ratio of 1:(0.7-0.9):(3-5), stirred at 75-85°C and 100-200 rpm for 3-5 h, allowed to stand at 145-155°C for 1-3 h, naturally cooled to room temperature, ground and sieved with 300-400 mesh, heated to 550-650°C at a rate of 1-3°C / min, kept warm for 1-3 h, and naturally cooled to room temperature to obtain porous nanoparticles. Magnesium oxide; mixing porous nano-magnesium oxide and anhydrous ethanol in a mass ratio of 1:(9-11), stirring at 20-30°C and 100-200rpm for 30-40min, adding a silver nitrate mixture of 14-16 times the mass of the porous nano-magnesium oxide at a uniform speed within 20-30min, continuing to stir for 3-5h and then centrifuging, washing with anhydrous ethanol for 3-5 times, and drying at 55-65°C for 47-49h to obtain silver-loaded porous nano-magnesium oxide; (2) 3-Butenetriethoxysilane and 45-55% ethanol solution were mixed at a mass ratio of 1:(8-10), the pH value of the solution was adjusted to 3-4 with glacial acetic acid, and ultrasonic dispersion was performed for 20-40 min to obtain 3-Butenetriethoxysilane alcoholysis solution; silver-loaded porous nano-magnesium oxide and anhydrous ethanol were mixed at a mass ratio of 1:(24-26), and ultrasonic dispersion was performed for 25-35 min, and 3-Butenetriethoxysilane alcoholysis solution with a mass of 3-4 times that of silver-loaded porous nano-magnesium oxide was added, and the mixture was stirred at 75-85°C and 410-430 r / min for 3-5 h, filtered, and filtered. The pre-modified silver-loaded porous nano-magnesium oxide was washed with ethanol and deionized water for 3 to 5 times, and dried at 70 to 80°C for 6 to 8 hours to obtain a pre-modified silver-loaded porous nano-magnesium oxide; the pre-modified silver-loaded porous nano-magnesium oxide, vinyltetramethyldisiloxane, chloroplatinic acid and toluene were mixed in a mass ratio of 1:(1.4 to 1.6):(0.03 to 0.04):(9 to 11), stirred in a nitrogen atmosphere at 85 to 95°C and 200 to 400 r / min for 6 to 8 hours, cooled naturally to room temperature and then centrifuged, washed with deionized water for 3 to 5 times, and dried at 45 to 55°C for 10 to 12 hours to obtain a modified silver-loaded porous nano-magnesium oxide; (3) Terephthalic acid, 5-nitro-1,3-phthalic acid and ethylene glycol were mixed in a molar ratio of 1:1:2.1, antimony trioxide (0.3-0.4 times the mass of terephthalic acid) was added, and the mixture was stirred at 235-245°C and 100-200 rpm for 2-4 hours under a nitrogen atmosphere, and the temperature was raised to 270-280°C and 90-110 Pa to continue the reaction for 3-5 hours, and the mixture was naturally cooled to room temperature, washed with deionized water for 3-5 times, and dried at 65-75°C for 10-12 hours to obtain nitropolyester; nitropolyester, palladium carbon with a palladium content of 10% and N-methylpyrrolidone were mixed in a mass ratio of 1:(0.6-0.8):(9-11), and the mixture was stirred at 20-30°C and 100-200 rpm for 23-25 ​​hours under a hydrogen atmosphere, and then filtered, and the nitropolyester was added. 99~101 times of deionized water, let it stand until the precipitate mass remains unchanged, then filter it, and dry it at 65~75℃ for 6~8h to obtain amino polyester; mix the amino polyester, glacial acetic acid and N,N-dimethylformamide in a mass ratio of 1:(0.01~0.02):(8~10), stir it at 20~30℃ and 200~300rpm for 1~2h, heat it to 75~85℃, add 1-allyl-1H-benzimidazole-2-carboxaldehyde, the ratio of the molar amount of aldehyde group in 1-allyl-1H-benzimidazole-2-carboxaldehyde to the molar amount of amino group in amino polyester is 1:1, continue stirring for 3~5h, cool it naturally to room temperature, add methanol 86~88 times of the mass of amino polyester, let it stand until the precipitate mass remains unchanged, then filter it, and dry it at 45~55℃ for 9~11h to obtain modified polyester; (4) The modified polyester is heated at 245-255°C by an internal mixer until it is melted, zinc chloride is added, and the ratio of the molar amount of zinc ions in the zinc chloride to the molar amount of nitrogen elements in the modified polyester is 1:

6. The mixture is stirred at 100-200 rpm for 5-15 min, and 0.6-0.8 times the mass of the modified polyester of modified silver-loaded porous nano-magnesium oxide and 0.01-0.02 times the mass of the modified polyester of azobisisobutyronitrile are added. The mixture is stirred for 10-20 min, and the mixture is rolled to a thickness of 0.4-0.6 mm by a calender, and the mixture is allowed to stand at 120-130°C for 10-12 h, and then naturally cooled to room temperature to obtain an antibacterial and waterproof polymer material for tablecloths.

3. A method for preparing an antibacterial and waterproof polymer material for tablecloth according to claim 2, It is characterized in that The silver nitrate mixed solution in step (1) is obtained by mixing silver nitrate, polyvinyl pyrrolidone and anhydrous ethanol in a mass ratio of 1:(1-3):(58-60), and stirring at 20-30° C. and 100-200 rpm for 3-5 hours.

4. The method for preparing an antibacterial and waterproof polymer material for tablecloth according to claim 2, It is characterized in that The reaction equation of the pre-modified silver-loaded porous nano-magnesium oxide in step (2) is:

5. The method for preparing an antibacterial and waterproof polymer material for tablecloth according to claim 2, It is characterized in that The reaction equation for the modified silver-loaded porous nano-magnesium oxide in step (2) is: 。 6. The method for preparing an antibacterial and waterproof polymer material for tablecloth according to claim 2, It is characterized in that The structure of the nitropolyester in step (3) is as follows: 。 7. The method for preparing an antibacterial and waterproof polymer material for tablecloth according to claim 2, It is characterized in that The structure of the amino polyester in step (3) is as follows: 。 8. The method for preparing an antibacterial and waterproof polymer material for tablecloth according to claim 2, It is characterized in that The reaction equation of the modified polyester in step (3) is: 。